Note-taking habits of 21st Century college students: implications for student learning, memory, and achievement. Issue 6 (3rd July 2019) - Morehead, Kayla; Dunlosky, John; Rawson, Katherine A.; Blasiman, Rachael; Hollis, R. Benjamin
ABSTRACT: Students rely on their notes to memorise and learn critical course content, and recent studies of note-taking state that most students take notes, citing a survey published in 1974. Over the past four decades, classrooms and note-taking technologies have evolved: students can take notes on electronic devices, and some classes are entirely online. Despite these changes, few studies have investigated their impact on note-taking habits. Given that note-taking is critical for student learning, the purpose of the present study was to update the literature on students' general note-taking behaviour and investigate the impact of these newer technological advances on note-taking. We surveyed 577 college students, using questions from prior surveys and new questions relevant to technology. As per prior studies, students still reported taking notes in classrooms, and as important, students reported flexibility in their note-taking by (a) using a notebook or a laptop depending on course demands and (b) often deciding not to take notes in online courses. Thus, students are flexible in their note-taking behaviour, but may not always make the best decisions about how and when to take notes.